2022
DOI: 10.1186/s12967-022-03382-y
|View full text |Cite
|
Sign up to set email alerts
|

Early and strong antibody responses to SARS-CoV-2 predict disease severity in COVID-19 patients

Abstract: Background Antibody response to SARS-CoV-2 is a valuable biomarker for the assessment of the spread of the virus in a population and evaluation of the vaccine candidates. Recent data suggest that antibody levels also may have a prognostic significance in COVID-19. Most of the serological studies so far rely on testing antibodies against spike (S) or nucleocapsid (N) protein, however antibodies can be directed against other structural and nonstructural proteins of the virus, whereas their freque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…The magnitude of antibody responses to SARS-CoV-2 have been shown to correlate with COVID-19 disease severity, where higher antibody responses develop during acute disease in more severe cases ( 13 , 15 ). Here, we correlated the anti-SARS-CoV-2 responses with the autoantigen responses and identified a range of degrees of correlation, with the majority showing weak to moderate positive correlations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of antibody responses to SARS-CoV-2 have been shown to correlate with COVID-19 disease severity, where higher antibody responses develop during acute disease in more severe cases ( 13 , 15 ). Here, we correlated the anti-SARS-CoV-2 responses with the autoantigen responses and identified a range of degrees of correlation, with the majority showing weak to moderate positive correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody responses to the Spike, S1, RBD and Nucleoprotein of SARS-CoV-2 have been shown to last up to a year post disease ( 9 12 ). In the initial months post infection, studies report the antibody responses to multiple SARS-CoV-2 antigens ( 13 , 14 ), however, less is known about the pattern of persistence to multiple antigens, within the same individuals, post 6 months. During the acute phase of infection, the level of antibody responses has been reported to be associated with disease severity, where those with more severe disease had greater antibody levels ( 13 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both anti-spike and anti-nucleocapsid IgE antibodies were significantly increased when compared to pre-pandemic controls (p<0.01 and p<0.0001, respectively; Figure 2D ). These results highlight that a subgroup of post-COVID-19 condition patients present a sustained immune response against SARS-CoV-2 antigens, with IgG, IgA and IgE levels similar or even increased when compared to those observed during active COVID-19 infections ( 23 , 24 ).…”
Section: Resultsmentioning
confidence: 52%
“…On another end, the study of antibody response to SARS-CoV-2 by screening virus antigen microarrays revealed that early IgA and IgG responses can constitute markers of acute disease severity ( 23 ). In addition, it was found that SARS-CoV-2 elicits IgE responses with levels positively correlating with severity thus suggesting a link between SARS-CoV-2 infection, degree of severity with mast cell activation ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%